Development and evaluation of a teacher training course with a focus on school inclusion (Research, Society and Development, 2020)
This article aimed to describe the main contributions of a continuing education course, structured to establish a space for dialogue and construction of knowledge on the theme of Inclusive Education. For this, the Problem Based Learning methodology was used, with conceptual maps as a proposal for learning evaluation, and a Likert attitudinal scale to evaluate the course. 24 coordinators of basic education of a city in the interior of Goiás participated in the proposal. The data, obtained from the paired evaluation of the maps before and after the course, were compared by the Wilcoxon marked posts test for paired samples. The results revealed statistically significant growth in the number of new concepts related to school inclusion in the post-course maps than in the pre-course (p